2020
DOI: 10.1155/2020/5401738
|View full text |Cite
|
Sign up to set email alerts
|

NBPF9 Gene May Be Involved in Congenital Hypopituitarism: A Whole-Genome Study of a Boy with Pituitary Stalk Interruption Syndrome and His Family

Abstract: Pituitary stalk interruption syndrome (PSIS) is a rare congenital defect manifesting as various degrees of anterior pituitary hormone deficiency. Scattered familial cases have been found, revealing some genetic variants. However, most of the previous research studies involved an affected sibling, and the gene spectra of the patients’ entire family have rarely been reported. We conducted a study of a family consisting of a PSIS patient with his unaffected sibling and healthy parents of Han Chinese background us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Fanconi's anemia, a rare autosomal recessive hematological disease, was also observed to be accomplished by PSIS [23], suggesting that gene mutations may play a signi cant role in the pathogenesis of PSIS. In humans, multiple gene mutations or sequence variants in PROP1, PTCH1, PTCH2, LHX4, POU1F1, HESX1, OTX2, SOX3, NBPF9 and GPR161 and so on, have been postulated to be involved in PSIS [24][25][26]. Brauner et al [27] performed exome sequencing in 52 PSIS cases and found that rare and novel genetic variants were identi ed in 75% of PSIS patients, which mainly involved in midline development and/or pituitary development or function, syndromic and non-syndromic forms of hypogonadotropic hypogonadism, syndromic forms of short stature, cerebellum atrophy with optic anomalies, axonal migration, and agenesis of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Fanconi's anemia, a rare autosomal recessive hematological disease, was also observed to be accomplished by PSIS [23], suggesting that gene mutations may play a signi cant role in the pathogenesis of PSIS. In humans, multiple gene mutations or sequence variants in PROP1, PTCH1, PTCH2, LHX4, POU1F1, HESX1, OTX2, SOX3, NBPF9 and GPR161 and so on, have been postulated to be involved in PSIS [24][25][26]. Brauner et al [27] performed exome sequencing in 52 PSIS cases and found that rare and novel genetic variants were identi ed in 75% of PSIS patients, which mainly involved in midline development and/or pituitary development or function, syndromic and non-syndromic forms of hypogonadotropic hypogonadism, syndromic forms of short stature, cerebellum atrophy with optic anomalies, axonal migration, and agenesis of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Kaygusuz et al described a novel FOXA2: c.616C >T, p.Q206X variant in one PSIS patient, causing impaired GLUT2-luciferase activation due to a truncated protein (19). Wang et al observed a significant reduction in LHX3 expression when NBPF9 was knocked down in human embryonic stem cells (25). Su et al found that silencing the CDC27 gene inhibits both migration and secretion functions in GH3 cells.…”
Section: Current Status Of Genetic Research On Psis Patientsmentioning
confidence: 99%